Usefulness of the kit Polycheck plus kit containing rBet v1 and rBet v2 allergens before birch pollen immunotherapy - Buczyłko, Krzysztof; Wagner, Aneta (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2011)
Aim : To evaluate the usefulness of specific IgE measurements by the Polycheck plus panel referred to allergy phenotype and the composition of specific immunotherapy preparations. The specific IgE set was composed of birch pollen, recombinant allergens Bet v1 and Bet v2, alder, hazel, timothy and mugwort pollen. Furthermore the kit was composed of latex, mite Dp and food allergens. Material and methods : In the study 36 persons with high level of specific IgE to birch pollen (over 0.35 kU/l) were examined, (20 men aged 11-59, mean age was 17.8 year and 16 women aged 18-52, mean age was 26.8). Results : Most of the group represented phenotype A = t3 (+), rBet v1 (+), rBet v2 (–) only with positive rBet v1 allergen (24/36, 72.2%). Patient with positive both allergens rBet v1 (+) and rBet v2 (+) represented phenotype B (2/36, 5.5%). Surprisingly 6 of 36 patients (16.6%) with positive sIgE t3 represented phenotype c with negative both measured epitopes. Phenotype D = t3 (+), rBet v1 (–), rBet v2 (+) involved 2/36 patients with allergy to profillin. Different condition of allergic specific IgE (birch, epitopes rBet v1 and rBet v2) was demonstrated among 36 patients with allergy to birch pollen. Conclusions : The investigation showed the need of expanded IgE measurements especially if the patients is potentially qualified to specific immunotherapy, widely standardized by Bet v1 allergen concentration measurements.